Association of food insecurity with myocardial infarction: a case-control study - soltani, sanaz; Dorosty Motlagh, Ahmad Reza; Siassi, Fereydoun; Babanezhad, Manoochehr; Qorbani, Mostafa; Aminianfar, Azadeh; Cheraghi, Ali (Progress in Nutrition, 2018)
Objective: There is a little evidence about association of cardiovascular diseases and food insecurity. This study was designed to examine the association of food insecurity and myocardial infarction (MI) in a sample of newly diagnosed cases in northern Iran. Methods: In this frequently matched case control study, 100 new MI cases (incident case) as a case group were compared with 100 persons as a control group matched by age, sex, and area of residence. Eighteen-item household food security questionnaire which is designed by United States Department of Agriculture (USDA) was used for assessing of food insecurity. The collected data was analyzed using Stata software by Logistic regression model. Results: After adjusting for the potential confounder variables including education, family history of MI, hypertension and smoking, multivariate logistic regression model showed that food insecurity was significantly associated with MI (OR=1.23, 95% CI: 1.09-1.40, P=0.001). Conclusions: The present study has shown that food insecurity is a significant predictor of MI and the odds of MI in food insecurity is higher than food secure cases.